2018
DOI: 10.1167/iovs.18-25369
|View full text |Cite
|
Sign up to set email alerts
|

Constriction of Retinal Venules to Endothelin-1: Obligatory Roles of ETA Receptors, Extracellular Calcium Entry, and Rho Kinase

Abstract: PurposeEndothelin-1 (ET-1) is a potent vasoconstrictor peptide implicated in retinal venous pathologies such as diabetic retinopathy and retinal vein occlusion. However, underlying mechanisms contributing to venular constriction remain unknown. Thus, we examined the roles of ET-1 receptors, extracellular calcium (Ca2+), L-type voltage-operated calcium channels (L-VOCCs), Rho kinase (ROCK), and protein kinase C (PKC) in ET-1-induced constriction of retinal venules.MethodsPorcine retinal venules were isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 75 publications
4
36
0
Order By: Relevance
“…The canonical role of the EDN system is to mediate vasoconstriction. EDN ligands are the most potent vasoactive peptides, and EDN has been shown to cause vasoconstriction through EDNRA expressed by vascular smooth muscle cells 4,7,8,43,44 . Importantly, JUN-JNK signaling has been shown to mediate neuronal death after ischemic insult [47][48][49][50][51] .…”
Section: Edn1 Induced Vasoconstriction and Rgc Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…The canonical role of the EDN system is to mediate vasoconstriction. EDN ligands are the most potent vasoactive peptides, and EDN has been shown to cause vasoconstriction through EDNRA expressed by vascular smooth muscle cells 4,7,8,43,44 . Importantly, JUN-JNK signaling has been shown to mediate neuronal death after ischemic insult [47][48][49][50][51] .…”
Section: Edn1 Induced Vasoconstriction and Rgc Hypoxiamentioning
confidence: 99%
“…In addition to the apoptotic RGC-autonomous mechanisms triggered by EDN signaling, the cell types that respond to EDN ligands to ultimately cause RGC death remain unknown. EDN ligands cause vasoconstriction by binding to EDNRA expressed by vascular smooth muscle cells 4,7,8,43,44 . Thinner retinal vessels and evidence of hypoxia have been demonstrated in animal models of chronic glaucoma 5,6,45,46 .…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Our previous study found that ET-1 causes marked constriction of porcine retinal venules through ET A receptors (ET A Rs) and extracellular Ca 2+ influx independent of L-type voltage-operated Ca 2+ channels. 20 We have also shown that hyperglycemia, a hallmark of diabetes, augments porcine venular constrictions to ET-1, U46619, and norepinephrine. 21 However, there has been no study addressing whether ET-1 affects the vasomotor tone of human retinal venules under euglycemia or hyperglycemia.…”
Section: Introductionmentioning
confidence: 69%
“…Techniques for identifying and isolating human and porcine retinal microvessels were similar to those used in our previous studies. 20,21,28 Briefly, retinal venules (1.0-1.5 mm in length without side branches) were identified based on the dark red deoxygenated blood in The sex, cardiovascular diseases, and medications and supplements to treat these diseases are provided for the five patients who donated retinal tissue for the vascular studies. the lumen and their thin vascular wall compared with the parallel arterioles containing bright red oxygenated blood and a thick vascular wall.…”
Section: Isolation and Cannulation Of Microvesselsmentioning
confidence: 99%
See 1 more Smart Citation